-2(2x-4)+9x=2(x-1)

Simple and best practice solution for -2(2x-4)+9x=2(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2x-4)+9x=2(x-1) equation:



-2(2x-4)+9x=2(x-1)
We move all terms to the left:
-2(2x-4)+9x-(2(x-1))=0
We add all the numbers together, and all the variables
9x-2(2x-4)-(2(x-1))=0
We multiply parentheses
9x-4x-(2(x-1))+8=0
We calculate terms in parentheses: -(2(x-1)), so:
2(x-1)
We multiply parentheses
2x-2
Back to the equation:
-(2x-2)
We add all the numbers together, and all the variables
5x-(2x-2)+8=0
We get rid of parentheses
5x-2x+2+8=0
We add all the numbers together, and all the variables
3x+10=0
We move all terms containing x to the left, all other terms to the right
3x=-10
x=-10/3
x=-3+1/3

See similar equations:

| -5+12k=11-4k | | 6x+40+20=180 | | 5x^2+4x+4=169 | | 4/9p=8/21 | | (X^2)(4x)=900 | | -18n-13=-15n+20 | | 2x+4=2(x-5)+14 | | $96+128.13$27.49+w=$300 | | 3=-2x-6x+3 | | 1+4x+3x=1 | | -45=7x-3-2x+38 | | 9.68x+21.6-6.23x=2.3x+7 | | -10+4x+4x=-66 | | 4n-9=4n-4n+9 | | 3(5x+8)=5(6x+9) | | 50=6x-x-10 | | 5x+68=5x+68 | | 3x-1+6x=-91 | | 24+0.79x=1 | | -4x-7+3x=-9 | | 6x^2=24=0 | | 15=6x+2x-9 | | -2.2+v/7=19.7 | | 54=6x+3x-9 | | 0=-5x=2x | | 8x-64=120 | | 9b-13=77 | | -6x+3-6x=87 | | x⋅x⋅x= | | 4n-4n-9=4n-4n+9 | | 6/7+2r+1/r-2=1/7 | | 30=-6x-x+9 |

Equations solver categories